1997
DOI: 10.1007/s004210050188
|View full text |Cite
|
Sign up to set email alerts
|

The development of an isokinetic squat device: reliability and relationship to functional performance

Abstract: This study was performed to determine the reliability and validity of a new isokinetic squat device in comparison to knee-extension tests performed using a Cybex. Athletic male subjects (n = 29) performed a series of isokinetic squat tests at 0.4 m.s-1, knee-extension tests at 1.05, 2.09 and 3.14 rad.s-1, and a 6-s stationary cycle test which was used as the measure of functional performance. The squat tests included a purely concentric squat without pre-load, a test with pre-load and a stretch-shorten cycle t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
2
10
0
1
Order By: Relevance
“…The results showed that the variation between the two test occasions was of a similar magnitude as reported earlier for reproducibility of concentric strength performance in squat (Munich et al 1997;Wilson et al 1997). Relevant reliability data for eccentric strength performance in squat are lacking.…”
Section: Machine and Mansupporting
confidence: 76%
“…The results showed that the variation between the two test occasions was of a similar magnitude as reported earlier for reproducibility of concentric strength performance in squat (Munich et al 1997;Wilson et al 1997). Relevant reliability data for eccentric strength performance in squat are lacking.…”
Section: Machine and Mansupporting
confidence: 76%
“…Such an approach is common in the literature (Thompson & Bemben, 1999;Walshe, Wilson, & Murphy, 1996;Wilson, Walshe, & Fisher, 1997). "Absolute" reliability refers to the degree, which repeated measures vary for individuals (Sale, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…It would appear that the procedures and equipment used to measure the dependent and independent variables were stable between trials and similar to other research testing new devices and procedures. For example, testing the reliability of an isokinetic squat device, Wilson et al (1997) reported inter-trial ICCs of 0.89-0.96 and coefficients of variation of 3.1-8.7% for a concentric and stretch-shorten cycle (SSC) squat. Lower correlation's were noted by Rahmani et al (2000), who reported intraclass correlation coefficients of 0.57-0.91 for peak force, peak velocity and peak power during a half squat on an isoinertial squat rack instrumented with an optical encoder.…”
Section: Reliabilitymentioning
confidence: 99%